Case report: Rechallenge with EGFR–TKIs after immunotherapy in EGFR–mutated non–small cell lung cancer with leptomeningeal metastasis - Qian, Chunfa; Zhang, Yuhai; Cheng, Wanwan; Zhang, Qingchao; Li, Mengzhen; Fang, Shencun (Frontiers in Oncology, 2022)
Rechallenge of epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) after PD-1 blockade failure was an effective therapy for non-small cell lung cancer (NSCLC) patients with resistance to EGFR-TKIs. The third-generation TKIs, like osimertinib and furmonertinib, can reach higher concentration in the cerebrospinal fluid (CSF) than other TKIs, and exhibit a beneficial effect in NSCLC patients with leptomeningeal metastases (LM) harboring sensitive EGFR mutation. Here, we report that two-stage IV pulmonary adenocarcinoma patients with LM harboring an EGFR L858R mutation benefit from the third-generation EGFR-TKIs rechallenge after immune checkpoint inhibitor (ICI) and anti-angiogenic agent combination therapy. Complete response (CR) to partial response (PR) of central nervous system (CNS) response was achieved immediately after the administration of furmonertinib and osimertinib. We conducted next-generation sequencing (NGS) and IHC to elucidate the evolution of driver mutations and the immune microenvironment. In conclusion, these two cases might provide a therapeutic strategy for further clinical practice. More research was needed to elucidate the resistance mechanisms and improve current treatment strategies in EGFR-mutated patients with LM.